Cervical cancer prevention by vaccination: review - González-Rodríguez, Julio Cesar; Cruz-Valdez, Aurelio; Madrid-Marina, Vicente (Frontiers in Oncology, 2024)
Routine use of human papillomavirus (HPV) vaccines is recommended in adolescents under 15 years of age worldwide. Still, effective programs remain suboptimal for several factors, making the WHO strategy to eradicate cervical cancer public health with an uncertain future. OBJECTIVE-To review the literature on the effectiveness, long-term protection, and safety of HPV vaccination programs and vaccination as adjuvant management. This review aims to describe the current state of vaccination programs and demonstrate the long-term protection and safety of vaccines implemented worldwide targeting adolescent girls, with the most recent published evidence of the three prophylactic HPV vaccinesbivalent (bHPV), quadrivalent (qHPV), and nonavalent (nHPV)-. We mainly focus on publications evaluating efficacy, dosing schemes, and HPV vaccination, as well as studies contributing to the mounting evidence for the real-life effectiveness of prophylactic HPV vaccines from several countries. FINDINGS -Human Papillomavirus vaccination programs have made remarkable strides in preventing HPV-related diseases; countries with robust vaccination efforts have witnessed substantial reductions in HPV-related diseases with a decline in high-grade cervical abnormalities and genital warts (54%-83%). However, global coverage remains uneven, with disparities between high-income (HICs) and low-income countries (LMICs). The long-term efficacy of the available human papillomavirus (HPV) goes up to 9.4 years and continues to be immunogenic and well tolerated with an excellent safety profile. CONCLUSIONS AND RELEVANCE-As these are crucial topics in HPV vaccination, it is essential to establish systems for continued monitoring of vaccine immunogenicity, efficacy, and safety over time.